Die Finanzierung von Sportarenen : Optionen für große und mittelgroße Projekte - Luca Rebeggiani; Sebastian Witte (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
Hosting the 2006 FIFA World Championship induced a boom in stadium investments in Germany. A second wave of smaller arena constructions can currently be observed across the country. These projects are promoted by smaller clubs of the first and the second Bundesliga, aiming not to fall behind the top clubs. The present paper gives an overview over recent financing models for large stadiums and then focuses on the special case of middle-size arenas.
Keywords: G31; H82; L83; 330; Sportökonomie; Stadionbau; Kommunale Investitionen; sports facilities; Sportanlage; Projektfinanzierung; Fußballsport; Public-Private Partnership; Kommunale Investition; Deutschland